Cuing Effects by Biologically and Behaviorally Relevant Symbolic Cues. (9th December 2020) - Yokoyama, Takemasa; Kato, Ryousuke; Inoue, Kazuya; Takeda, Yuji
Abstract: This study investigates whether symbolic cues that are relevant biologically (e.g., eye gaze) and behaviorally (e.g., arrows) have analogous characteristics and function similarly in terms of attentional resource consumption. Both cues induce attentional orienting when they do not indicate a target location, but it remains unclear whether cuing effects by those cues have similar characteristics. We recently found that cuing effects by non‐predictive gaze cues remain intact when a spatial working memory task is concurrently performed. Here, we examined whether non‐predictive arrow cues induce cuing effects when spatial working memory is occupied. To this end, we conducted a dual‐task paradigm consisting of cuing (gaze and arrow) and spatial working memory tasks. In the cuing task, participants judged whether a peripherally presented target was positioned at left or right while ignoring the centrally presented cues. In the spatial working memory task, participants performed a change‐detection task. In the dual‐task condition, participants performed the two tasks on the same trial. In Experiment 1, we observed cuing effects by both gaze and arrows, even when the spatial working memory task was concurrently performed, although reaction times were overall faster in the gaze than arrow conditions. In Experiment 2, we rejected the possibility that automatic visual orienting found in Experiment 1 had been induced by simple motion perception of gaze and arrow cues. The present study suggests that biologically and behaviorally relevant symbolic cues have analogous traits with respect to resource processing.